From Webtoon to Vocabulary: A Case Study Comic Translation for Language Enrichment in Gen Z - Ruqoyyah, Siti; Irmayani (Universitas Pendidikan Ganesha, 2025)
English as a Foreign Language (EFL) classrooms, vocabulary acquisition continues to encounter obstacles because of students’ low engagement with traditional methods, as well as contextual limitations. As Generation Z learners become more honed to digital and visual culture, an urgent need arises to align strategies that meet the learners in this context. This study seeks to analyse, critique, and interpret to potentials of Webtoon translation based pedagogy for enrichment of vocabulary knowledge and to enhance motivation and intercultural awareness for Gen Z learners. The research utilized a qualitative case study design to provide an in-depth understanding of students' experiences and responses to authentic learning situations. Data were collected from 40 undergraduate students through language vocabulary pre- and post-tests, classroom observations, reflective journals, and semi-structured interviews. Quantitative test data were analyzed using descriptive statistics and a t-test to determine vocabulary gains, while qualitative data were coded then subjected to thematic analysis to identify recurring themes about: translation strategies, challenges to learning, and motivating factors. Based on the findings, vocabulary mastery increased significantly following the use of the Webtoon intervention. Statistically significant gains were made by learners in contextualization of vocabulary, understanding idiomatic expressions, and ability to remember words or phrases. Furthermore, qualitative feedback suggested that the enriched and multimodal possibilities of Webtoons were effective in promoting deeper cognitive processing and motivating learners to engage with the targeted vocabulary. However, challenges existed in interpreting slang and cultural context, plus technical difficulties with digital access were evident.